(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
This study has four interrelated main objectives. First, to examine the distribution of the variables of nutrient content, water consumption, exercise goal, and exercise outcome expectation period. Second, to compare water consumption levels for each of the nutrient content and exercise goal variables. Third, to determine students’ attitudes towards sports. Fourth, to evaluate the potential impact of the variables of nutrient content, exercise goal, expectation time after exercise, and level of water consumption on attitudes towards sports. 225 female university students participated voluntarily. Personal information form and attitudes scale towards sport were used as data collection tools. As a result, nutrient content, water consumption, exercise goal, and exercise outcome expectation period were examined separately within themselves, there was a statistically significant difference (p<.001). The relationship between nutrient content (p<.05) and exercise goal (p<.001) variables with the amount of water consumption was statistically significant. Students have high scores in attitudes towards sport scale. Excessive carbohydrate consumption should be avoided, and information should be given that <1 L/day water consumption is unhealthy.